The Development of Chemo-entrepreneurship Oriented Material Books to Analyze Cognitive Abilities of Grade 10 Students in Redox Reaction - Maula Najikh Wildana; Sri Susilogati Sumarti; Endang Susilaningsih (International Conference on Science, Education, and Technology, 2021)
The aim of this research is to develop chemo-entrepreneurship-oriented teaching materials that appropriate and effective to analyze students’ cognitive ability. This is Research and Development method with ADDIE model design. Subjects were students of class X MIPA 1 Madrasah Aliyah Negeri 1 in Semarang City. The research was started out from January to May 2021. Data collection methods are by observation, questionnaires, tests, and project methods. The instrument used include interview sheets, instrument validation sheets, questionnaire responses, and cognitive evaluation instruments. Data analysis techniques include analysis of interview sheets, instrument validation, analysis of the effectiveness of teaching materials, and analysis of questionnaire responses. The results is an appropriate and effective CEP-oriented teaching materials that used to teach in corona virus pandemic era. Teaching materials get an average validation score of 49 out of 52. Teaching materials also get positive responses from teachers with score 35 out of 40 and positive responses from students with an average score of 38.53 out of 48. The results also mention good cognitive abilities of students where 26 of 30 students or 87% students passed the minimum score, the highest score was 87, the lowest score was 53, and the average score was 75. It means that developed material book have a good score and effective to help teacher explain chemistry with interdisciplinary approaches.